EFFECT OF GROUP ACTIVITIES THERAPY ON THE IMPROVEMENT OF BASIC SOCIAL SKILLS IN SCHIZOPHRENIA PATIENTS IN RSJD Dr. RM. SOEDJARWADI CENTRAL JAVA 2015 - Hartono, Hartono (EMPATHY Jurnal Fakultas Psikologi, 2015)
ABTRACK-This study examines whether group activity therapy can improve basic social skills of schizophrenic patients. This study is a quantitative and using SPSS version 16.0. Qualitative analysis using observation and interviews. The design of this study are randomized control group pretest - posttest design - followup. Five subjects diagnosed with schizophrenia and hospitalized. The independent variable group is activity therapy and dependent variables is social skills base. This research analyzed by Mann Whitney U test and Friedman test. The results are shown to improve basic social skills schizophrenic patients. Data processing results show the level of significance, the results of Mann Whitney test to gain score of the experimental group and the control group significantly, meaning that the intervention of group activity therapy can improve basic social skills scale score the schizophrenia patients in experimental group. Analysis results of the basic social skills scale between pretest and posttest scores experimental group and the control group are significantly, it means that there are significantly differences in basic social skills scores schizophrenic patients between pretest and posttest scores in experimental group and control groups, in followup the results of the analysis of Friedman test also showed significant result.Keywords: group activity therapy, social skills base, schizophrenic patients